Mechanistic study on radiation‐induced grafting into fluorinated polymer solid films using a swelling‐induced detachment of grafted polymers. Issue 1 (6th December 2020) - Ko, Beom‐Seok; Yoshimura, Kimio; Hiroki, Akihiro; Maekawa, Yasunari
Abstract: The radiation‐induced graft polymerization (RGP) of styrene into poly(ethylene‐ co ‐tetrafluoroethylene) films was performed at various monomer concentrations and solvents at 60 °C. The grafted polystyrene ( g ‐PS) was isolated using the swelling‐induced detachment phenomenon, and the number‐averaged molecular weight ( Mn ) and the number of g ‐PS ( Np ) were determined using gel permeation chromatography. The Mn increased consistently with an increase in the grafting time up to 2–3 hours, indicating very low termination rates, which was a result of the "gel effect". This is the first direct evidence of the gradual Mn increase over time using RGP in thermally and chemically stable polymer films such as fluorinated polymers. When the Mn and Np were plotted as a function of the degree of grafting ( DOG ), sudden Np drops along with rapid Mn increases were observed in the DOG region of 80–90%, indicating negligible initiation and propagation; however, a recombination termination between two propagating g ‐PS radicals dominated the later part of the grafting process. Further increases in both Mn and Np were observed subsequently, implying that reinitiation and propagation events were triggered by morphological changes, as observed by small‐ and ultrasmall‐angle X‐ray scattering experiments, which liberated the dormant radicals from the lamellar crystals. Abstract : The mechanism of radiation‐induced graft polymerization into fluorinated polymer films is revealed by a systematic analysis of grafted polymers, which can be isolated using a swelling‐induced detachment phenomenon. Changes in the number‐averaged molecular weight ( Mn ) and the number of grafted polymers, show the gradual Mn increase over hours, indicating the living nature of the propagating radicals. At the final step, reinitiation and propagation events are triggered by morphological changes, which liberated dormant radicals from the lamellar crystals.